DIABETES MELITUS BECOME A HEALING DISEASE IN COVID-19 PATIENTS (SYSTEMATIC REVIEW) - WAHYU WAHDANA; Hotma Rumoharbo; Murtiningsih Murtiningsih; Yayat Suryati; Hikmat Rudyana (NHM PRESS, 2021)
Background: Diabetes mellitus (DM) is a chronic disease characterized by high blood sugar levels and is one of the most commonly reported comorbidities and is a risk factor for increasing the severity of Covid-19 infection. Diabetes is the second comorbidity that is often found in Covid-19 patients in Indonesia with 35.5% cases, 24.1% recovery, and 10.6% death. This study aims to conduct a systematic review based on the results of studies that have been published so far about DM disease complicating healing, exacerbating disease conditions, and causing death in Covid-19 patients.Method: The research used systematic review on several electronic databases on the subjects of Covid-19 patients with diabetes who had changed disease conditions. Search for articles using the PEOS strategy and using the keyword